Mellem blod, lort, kollegaer og ledelse: Prekær stil i Kenneth Jensens Tragedie plus tid gange ni og Kristian Lundbergs Yarden - Obbekær, Troels (Passage - Tidsskrift for litteratur og kritik, 2020)
This article investigates the ambivalence embedded in the literary motif of the precarious autobiographical narrator’s distanced and solidary gaze on the precarious ‘others’ and their bodies. In analyzing Tragedie plus tid gange ni (2017) and Yarden (2009), the article argues that through ‘precarious narration’ – an unreliable first-person narrator’s inability to understand the other characters and their distress – the novels lead to an understanding of the cultural divisions and work-related experiences of the precariat.